A Descriptive Study of Managers' Perceptions of the Use of Financial Statements in the HR Management Decision-Making Process - Pertiwi, Wike (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The purpose of this study is to explore human resource (HR) managers' perceptions of using financial statements in HR decision-making, particularly in compensation, workforce planning, and budgeting. The research design employed a qualitative approach involving interviews with HR managers to understand how financial data is interpreted and applied in strategic decisions. The methodology focused on identifying the barriers HR managers face, including financial literacy limitations and organizational silos, that hinder the effective integration of financial data into HR practices. The findings reveal significant variability in financial literacy among HR managers, directly influencing their ability to leverage financial data. While some managers demonstrate a strong understanding of financial statements, others rely heavily on operational metrics. The study highlights the need for organizational improvements, particularly in fostering collaboration between HR and finance departments, to ensure more informed and aligned decision-making. In terms of implications, the study offers practical recommendations for improving HR decision-making by increasing financial literacy through targeted training programs and promoting interdepartmental collaboration. This research contributes to both theory and practice by emphasizing the importance of financial data in HR strategies, with implications for more integrated HR and financial management approaches.